The rightest word of Imam MALIK’s saying about the rising of ALLAH on his mighty throne - ben Salem, Rachid Ben Jilali (Journal of Islamic Sciences, 2021)
This research deals with the belief of imam MALIK and his methodology of the attributes of ALLAH, by explaining his famous saying about the rising of ALLAH on his throne. Indeed; ALIMAM MALIK (may ALLAH have mercy on him) demonstrated that the rising of ALLAH the almighty on the throne relying on the texts of QURAN and SUNNAH of the prophet (peace be on him) this rising suit the majesty of ALLAH without going deeper in its forms, because the forms of attributes are from the unseen world. Issues which are incomprehensible to human minds, furthermore one is allowed to question about the manner of the rising of ALLAH on his throne, and also about all other attributes.